Occurrence of genus Scenedesmus Mayen (Chlorophyceae) from East Nepal - Rai, Shiva Kumar (Nepalese Journal of Biosciences, 2013)
A total 18 taxa of genus Scenedesmus (Chlorococcalean algae) has been reported from the freshwater habitats of east Nepal. Among them, 5 taxa viz., Scenedesmus abundans, S. arcuatus var. platydiscus, S. disciformis, S. hystrix, and S. perforatus are new records for Nepal. A total 12 taxa viz., S. acuminatus, S. acutus, S. armatus var. asymmetricus, S. bernardii, S. bijuga, S. bijugatus var. graevenitzii, S. dimorphus, S. opoliensis, S. prismaticus, S. quadricauda var. longispina, S. quadricauda var. westii and S. smithii are first time reported from east Nepal.